Cyclic properties and impedance analysis of (Li, Na, K)NbO3-based multilayered piezoceramics. (27th August 2020) - Nishiyama, Hiroshi; Kakimoto, Ken-ichi; Hatano, Keiichi; Kishimoto, Sumiaki; Sasaki, Nobuhiro
Abstract: (Li, Na, K)NbO3 -based multilayered piezoceramics were characterized by performing unipolar polarization electric field measurements and impedance spectroscopy. Subjecting an as-poled sample to up to 10 7 cycles in an applied 4 kV mm −1 unipolar cyclic field at 100 °C reduced its polarization by 8.9%. The impedance spectra of as-sintered, as-poled, and fatigued samples were acquired and analyzed. Two relaxation processes reported to occur in single-layered (Na, K)NbO3 -based ceramics were identified. They occurred at inner domains and interfaces, including domain walls (DWs) and grain boundaries, below the Curie temperature ( T C, 450 °C). The electrical properties of the samples were evaluated by two resistance-constant phase element (2 R-CPE) equivalent circuit analysis. The results indicated that DW pinning was the primary cause of unipolar fatigue.